Decreasing Resource Utilization without Compromising Care through Minimizing Preoperative Laboratories. Issue 7 (July 2018) - Beliveau, Lauren; Buddenhagen, Denise; Moore, Billy; Davenport, Daniel; Burton, Mandy; Duane, Therese
Approximately 18 billion dollars is spent annually on preoperative testing. The purpose of this study was to determine whether implementation of an algorithm aimed at minimizing pre-operative tests resulted in decreased costs without compromising care. We performed a pre–post trial comparing January 2016 to April 2016 with May 2016 to July 2017. In May 2016, an algorithm was instituted in which laboratories were canceled based on an algorithm that incorporated patient and procedural factors. Total number of laboratories canceled before orthopedic, urologic, or general surgical procedures was documented. Case cancellations during this time were recorded. There were 22, 175 laboratories during the study time frame. There was a significant decrease of 2.4 per cent in expected laboratories in the post-intervention group. There was an overall cost savings of 33, 032.00. The per cent of patients who were seen in preoperative testing clinic and still needed medical optimization decreased after algorithm implementation (3.3% vs 2.1% P < 0.01). No cases were canceled because of lack of laboratory information. An algorithm for selective preoperative laboratory testing provides overall cost savings. Decreasing the number of unnecessary laboratories ordered reduced case cancellations. Instituting an algorithm for preoperative laboratory testing is cost-effective without compromising care.